2017
DOI: 10.4102/ac.v17i1.396
|View full text |Cite
|
Sign up to set email alerts
|

Social media in tourism: Establishing factors influencing attitudes towards the usage of social networking sites for trip organisation

Abstract: Purpose: The main aim of this study was to determine the attitude towards the use of SNSs for trip organisation and its precursors. Problem investigated: Tourism organisations and destination policy makers need to understand factors that influence tourist use of SNSs for trip organisation in order for them to be able to effectively utilise SNSs. Methodology: The methodological approach followed was exploratory and quantitative in nature. Data were collected from a total of 340 respondents using a structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Thus, social network is presented as a kind of social structure consisting of a group of nodes, which are social objects (people or organizations), as well as the connections between them (social relationships) [17][18][19][20].…”
Section: Results and Debatementioning
confidence: 99%
“…Thus, social network is presented as a kind of social structure consisting of a group of nodes, which are social objects (people or organizations), as well as the connections between them (social relationships) [17][18][19][20].…”
Section: Results and Debatementioning
confidence: 99%
“…These findings are new to the body of hotel social media research, and contribute to knowledge about the factors that influence consumers' attitude towards using social network sites in terms of the selection of hotels, largely because the study is among the first to examine those factors in the context of using social media with regard to hotel selection in the UAE. Most research tends to concentrate on the use of social media sites in the selection of tourism destinations (Hua, 2017), festival attendance (Kim, Osman, Gyehee & Hande, 2018) and trip organization (Matikiti, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that compliance, internalization and identification are determinants of guests' attitudes toward a Facebook hotel page. Matikiti, Mpinganjira & Roberts (2017) showed that attitude towards the use of SNS for trip organization is affected by the perceived benefits, with perceived usefulness having the greatest influence. Hua, Ramayah, Teoh & Cheah (2017) modeled the use of social media as a tool to select tourism destinations.…”
Section: Social Media Users In the Uaementioning
confidence: 99%
“…This finding reaffirmed several arguments across a range of research that females use more social media than males (Nunkoo, Juhaweer & Rambhunjun, 2013). Although empirical evidence had established the practical benefits of social media technology, the heterogeneous nature consumers (openness and neuroticism) and device perceptions (technology, fashion, or both) were identified to be critical moderators of the effects (Matikiti, Mpinganjira & Roberts-Lombard, 2017).…”
Section: 1) Individual-level Factorsmentioning
confidence: 99%
“…The concern about privacy threats may prevent the cultivation of the technological trust, which can result in feelings of vulnerability and uncertainty that constituted the psychological barriers of risk inhibiting adoption (Connolly & Bannister, 2007). Most studies hypothesised that privacy and data security risks would affect consumer attitude towards social media technology (Ravindran et al, 2018;Matikiti, Mpinganjira & Roberts-Lombard, 2017). Hence, people who perceived risks to be associated with using SNS, these individuals would develop a negative attitude towards the sites.…”
Section: Privacy Riskmentioning
confidence: 99%